The Cenozoic European Polyplacophora (Mollusca) - Dell’angelo, Bruno; Sosso, Maurizio; Taviani, Marco (Zootaxa, 2025)
The European Cenozoic Polyplacophora has been reviewed, with a focus on the Oligocene to Pleistocene paleontological record. Based upon literature records and institution and private collections, we have critically revised 171 taxa, 152 of which are considered taxonomically valid. Among these, 35 are extant species with a fossil record, and 19 are of unclear taxonomic position. Nineteen species are described as new: Lepidopleurus pseudocajetanus sp. nov. (Miocene/Pleistocene), Lepidopleurus reitanoi sp. nov. (Pleistocene), Leptochiton corticellii sp. nov. (Pleistocene), L. prudenzae sp. nov. (Pliocene), L. rumani sp. nov. (Miocene), Hanleya fratrum sp. nov. (Pleistocene), H. sirenkoi sp. nov. (Pleistocene), Ischnochiton cluzaudi sp. nov. (Miocene), I. krohi sp. nov. (Miocene), I. lesporti sp. nov. (Miocene), I. sigwartae sp. nov. (Pleistocene), Stenosemus juliuspisai sp. nov. (Pliocene-Pleistocene, Recent?), S. praedolii sp. nov. (Miocene/Pleistocene), S. rossoae sp. nov. (Pleistocene), S. vendrascoi sp. nov. (Miocene), Rhyssoplax garillii sp. nov. (Pliocene/Pleistocene), Lepidochitona kieli sp. nov. (Miocene), Lepidochitona saitoi sp. nov. (Pleistocene), and Acanthochitona mathiasi sp. nov. (Miocene). The stratigraphic distribution of the genus Lucilina Dall, 1882 is extended to the Lower Oligocene. One of the species introduced herein (Stenosemus juliuspisai sp. nov.) is likely still living in the Mediterranean Sea. This revision serves as a necessary step in establishing a foundational baseline for understanding the evolutionary and biogeographic patterns of Polyplacophora in European seas through time up to the present.